Creatine supplementation: impact on cycling sprint performance - Levesque, D. G.; Kenefick, R. W.; Quinn, T. J. (Journal of Exercise Physiology online, 2007)
To date, studies involving creatine supplementation (CrS) and repetitive sprint performance have included either complete rest or passive recovery between sprinting efforts. In competitive cycling, criteriums are popular events, which require intermittent all out sprinting followed by "recovery cycling" normally maintained at approximately lactate threshold (LT) intensity. The purpose of this investigation was to determine if CrS would enhance repetitive cycling sprint performance with near LT activity between sprinting bouts. Nine male cyclists performed three 25.2-kilometer sprint trials (ST1, ST2, ST3), consisting of five 200-meter sprints every five kilometers. Inter-sprint intensity was maintained near LT wattage (±20 W). The first ST served as the control where no supplement was given. In double blind fashion, subjects were then randomly assigned to receive either creatine (20 g·d-1 for 6 days) or a placebo supplement preceding ST2 and the opposite supplement prior to ST3 after a five-week washout period. A repeated-measures ANOVA showed that time, peak power, and mean power for the 200-meter sprints did not improve significantly after CrS. These results suggest that CrS for increased performance involving repetitive sprints is not effective when intense activity occurs between sprinting bouts and would therefore not be recommended for such competitions. ABSTRACT FROM AUTHOR